LPG stove and fuel intervention among pregnant women reduce fine particle air pollution exposures in three countries: Pilot results from the HAPIN trial. (15th December 2021) - Liao, Jiawen; Kirby, Miles A.; Pillarisetti, Ajay; Piedrahita, Ricardo; Balakrishnan, Kalpana; Sambandam, Sankar; Mukhopadhyay, Krishnendu; Ye, Wenlu; Rosa, Ghislaine; Majorin, Fiona; Dusabimana, Ephrem; Ndagijimana, Florien; et al.
Abstract: The Household Air Pollution Intervention Network trial is a multi-country study on the effects of a liquefied petroleum gas (LPG) stove and fuel distribution intervention on women's and children's health. There is limited data on exposure reductions achieved by switching from solid to clean cooking fuels in rural settings across multiple countries. As formative research in 2017, we recruited pregnant women and characterized the impact of the intervention on personal exposures and kitchen levels of fine particulate matter (PM2.5 ) in Guatemala, India, and Rwanda. Forty pregnant women were enrolled in each site. We measured cooking area concentrations of and personal exposures to PM2.5 for 24 or 48 h using gravimetric-based PM2.5 samplers at baseline and two follow-ups over two months after delivery of an LPG cookstove and free fuel supply. Mixed models were used to estimate PM2.5 reductions. Median kitchen PM2.5 concentrations were 296 μg/m 3 at baseline (interquartile range, IQR: 158–507), 24 μg/m 3 at first follow-up (IQR: 18–37), and 23 μg/m 3 at second follow-up (IQR: 14–37). Median personal exposures to PM2.5 were 134 μg/m 3 at baseline (IQR: 71–224), 35 μg/m 3 at first follow-up (IQR: 23–51), and 32 μg/m 3 at second follow-up (IQR: 23–47). Overall, the LPG intervention was associated with a 92% (95% confidence interval (CI): 90–94%) reduction in kitchen PM2.5 concentrations and a 74% (95% CI: 70–79%) reduction in personal PM2.5 exposures. Results were similar for each site. Conclusions: The intervention was associated with substantial reductions in kitchen and personal PM2.5 overall and in all sites. Results suggest LPG interventions in these rural settings may lower exposures to the WHO annual interim target-1 of 35 μg/m 3 . The range of exposure contrasts falls on steep sections of estimated exposure-response curves for birthweight, blood pressure, and acute lower respiratory infections, implying potentially important health benefits when transitioning from solid fuels to LPG. Highlights: There was high uptake of an LPG stove and fuel intervention in 3 rural settings. The LPG intervention was associated with a 92% reduction in kitchen PM2.5 levels. The intervention was associated with a 74% reduction in personal exposure to PM2.5 Maternal PM2.5 exposure was reduced to the WHO annual interim target-1 of 35 μg/m 3 . Results from 3 countries indicate switching to clean fuel could improve health. Abstract : Capsule summary: LPG stove and fuel intervention can reduce kitchen area and personal PM2.5 exposure levels in a pilot study of clean cookstove intervention trial. This strongly suggests switching to clean cook can improve health.